2005
DOI: 10.1128/ec.4.10.1654-1661.2005
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans -Conditioned Medium Protects Yeast Cells from Oxidative Stress: a Possible Link between Quorum Sensing and Oxidative Stress Resistance

Abstract: Candida albicans, the most frequent fungal pathogen of humans, encounters high levels of oxidants following ingestion by professional phagocytes and through contact with hydrogen peroxide-producing bacteria. In this study, we provide evidence that C. albicans is able to coordinately regulate the oxidative stress response at the global cell population level by releasing protective molecules into the surrounding medium. We demonstrate that conditioned medium, which is defined as a filter-sterilized supernatant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 68 publications
5
97
0
1
Order By: Relevance
“…These genes function in diverse stress responses. These mutants are interesting because farnesol treatment leads to increased survival after heat shock (17) and confers protection from oxidative stress (5,6,32). Osmotic stress protection is also mediated by the cAMP/PKA pathway (4,5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes function in diverse stress responses. These mutants are interesting because farnesol treatment leads to increased survival after heat shock (17) and confers protection from oxidative stress (5,6,32). Osmotic stress protection is also mediated by the cAMP/PKA pathway (4,5).…”
Section: Resultsmentioning
confidence: 99%
“…It blocks the transition from yeast to filaments once it accumulates above a threshold level (3). It also has an inhibitory role in biofilm formation (4) and a protective role against oxidative stress (5,6). In addition, very high levels of farnesol can increase chlamydospore formation (7), while even very low levels of farnesol induce cell death by necrosis in opaque cells (8).…”
mentioning
confidence: 99%
“…The lag phase after C. albicans cells are transferred to either hypha-inducing and noninducing media is decreased when tyrosol is present in the medium (8). Tyrosol does not appear to have a role in detoxifying oxidants in the medium (98). Microarray studies showed that tyrosol prevents the temporary decrease in expression of genes involved in DNA replication, chromosome seg-regation, and cell cycle regulation that normally occurs during that lag phase that follows culture dilution (8).…”
Section: Other Fungal Autoregulatory Moleculesmentioning
confidence: 99%
“…In addition to its effects on hyphal development, farnesol (35 M) confers some protection to hydrogen peroxide, and this effect does not appear to be due to the increased transcription of genes involved in the oxidative stress response, including superoxide dismutase (SOD1 and SOD2) and catalase (CAT1) (98). The presence of farnesol does lead to the increased transcription of the genes encoding the CDR1 and CDR2 efflux pumps (15).…”
Section: Albicans and Autoregulationmentioning
confidence: 99%
“…In a similar way it further regulates oxidative stress response of C. albicans (Deveau et al 2010). Farnesol was shown contributing to the increased resistance of C. albicans populations after contact to higher levels of reactive oxygen species (ROS) (Westwater et al 2005). Extracellular ROS are produced by several organisms and, accordingly, effective defending strategies are vitally important for competing fungal species.…”
mentioning
confidence: 99%